Barreiras no processo de implatação das normas brasileiras de contabilidade aplicadas ao setor público - nbcasp: uma análise do processo nas Universidades federais brasileiras - Cruz, Juliana Mateusa Meira [UNIFESP] (2015)
With the growing negotiations between national governments and transnational institutions from different regions of the world, there is the need for an accounting harmonization, not only for private companies to IFRS, but for the entire public sector of countries, based on IPSAS. In Brazil, the process of convergence with international accounting standards in the public sector began in 2008 with the editing and publishing of the first NBCASP - Brazilian Accounting Standards applied to the Public Sector. Since then, the federal government has been working to advance the implementation of these standards throughout the country, the three levels of government: municipal, state and federal. Brazil has walked in this process; however, the transition has not been easy. Cultural differences, organizational, legal, the specific objectives, the origin of the funds, the regulatory authorities, training professionals and the political and administrative environment of each country make it difficult to process. The literature brings some factors that favor the emergence of transitional barriers in different areas: contextual, behavioral, content and capacity (LUDER, 1992 CHRISTENSEN, 2002 and OUDA, 2004). According to these factors, there may be transitional barriers that may be of practical or conceptual nature to be faced (OUDA, 2010). The main objective of this research is to know the main transition barriers that have hindered the deployment process of international standards of public accounting in Brazilian federal universities. In the perception of respondents, the main practical barriers to be overcome are: a) the culture of bureaucratic management; b) the resistance to change; c) the overvaluation of the budget at the expense of equity; and d) the lack of qualification of servers. Among the conceptual barriers of greatest impact in the process, they included: a) the difficulty of identification and evaluation of assets; and b) the lack of accountability for results and goals. In contradiction to the lack of accountability for results and goals, a large proportion of respondents (90.48%) believes the new standards require a new server profile engaged in public accounting, and the essential characteristics of this new profile are the motivation for learn and multidisciplinary knowledge; ie even without incentives from the government in the perception of respondents, there is the need to motivate and seek new knowledge to contribute to the process of implementation of NBCASP in Brazilian federal universities.